Traditions and innovations in hospitality industry - Yakymenko, Olena (My University, 2014)
There is always a fine line to be walked when comparing tradition to innovation. In some ways, consumers embrace innovation as a time saving tool or a way of making life easier, but on the other hand, tradition is what drives consumers to make certain choices over others.
Keywords: innovation (hotel and restaurant complex); індустрія гостинності; hospitality industry; інновації (готельно-ресторанний комплекс); кафедра іноземних мов професійного спрямування